Association between vitamin D and inflammatory bowel diseases - Baz-López, Alina (2023)
Vitamin D is a hormone known for a long time, for its effects on bone health and the regulation of phosphorus and calcium metabolism. Since the discovery of receptors for this molecule in a large number of cells in the body, the field has been opened for the study of its effects on the immune system. Its relationships with the cells of the immune system, genes, and microbiota cause great interest in relation to immune-mediated diseases. Many data indicates that this vitamin has preventive, modulating and controlling effects of the adverse effects of Inflammatory Bowel Diseases (IBD) on bone health, although it is difficult to definitively demonstrate causality. In this review, we try to summarize the current situation and controversial issues in this interesting field, focusing on inflammatory bowel diseases.